Chemical approach to fabrication of semicontinuous Au nanolayers for SERS applications - Bartosewicz, Bartosz; Gajda-Rączka, Magdalena; Jankiewicz, Bartłomiej Jerzy (Photonics Letters of Poland, 2013)
The fabrication of semicontinuous Au films on glass slides by using a chemical approach was carried out to test their surface enhanced Raman scattering (SERS) properties. Scanning electron microscopy (SEM) and UV-Vis-NIR spectroscopy were used for characterization of the morphology and optical properties of fabricated gold nanolayers. The SERS properties of Au films were tested using p-mercaptoaniline (pMA). A maximum estimated SERS enhancement factor greater than 106 can be achieved for this compound. SERS enhancement factors are shown to be dependent on the Au nanolayers’ morphology. Full Text: PDF References B. Sharma, R. R. Frontiera, A-I. Henry, E. Ringe, R. P. Van Duyne, "SERS: Materials, applications, and the future", Mater. Today 15, 16 (2012). CrossRef G. C. Schatz, M. A. Young, R. P. Van Duyne, "Electromagnetic Mechanism of SERS", Topics in Applied Physics; Vol.103, pp. 19-46, DirectLink ; Kneipp, K., Moskovits M., Kneipp, H. Eds., "Surface Enhanced Raman Scattering Physics and Applications" (Springer; New York, 2006). DirectLink T. Vo-Dinh, TrAC-Trend. Anal. Chem. 17, 557 (1998). CrossRef G. A. Baker, D. S. Moore, "Progress in plasmonic engineering of surface-enhanced Raman-scattering substrates toward ultra-trace analysis", Anal. Bioanal. Chem. 382, 1751 (2005). CrossRef M. Fan, G. F. S. Andrade, A. G. Brolo, "A review on the fabrication of substrates for surface enhanced Raman spectroscopy and their applications in analytical chemistry", Anal. Chim. Acta 693, 7, (2011). CrossRef K. Kneipp, Y. Wang, H. Kneipp, L.T. Perelman, I. Itzkan, R. Dasari, M.S. Feld, "Single Molecule Detection Using Surface-Enhanced Raman Scattering (SERS)", Phys. Rev. Lett. 78, 1667 (1997). CrossRef J. P. Camden, J. A. Dieringer, J. Zhao, R. P. Van Duyne, "Controlled Plasmonic Nanostructures for Surface-Enhanced Spectroscopy and Sensing", Acc. Chem. Res. 41, 1653 (2008). CrossRef V. P. Drachev, M. D. Thoreson, V. Nashine, E. N. Khaliullin, D. Ben-Amotz, V. J. Davisson, V. M. Shalaev. "Adaptive silver films for surface-enhanced Raman spectroscopy of biomolecules", J. Raman Spectrosc. 36, 648 (2005). CrossRef D. J. Semin, K. L. Rowlen, "Influence of vapor deposition parameters on SERS active Ag film morphology and optical properties", Anal. Chem. 66, 4324 (1999). CrossRef J. B. Jackson, N. J. Halas. "Surface-enhanced Raman scattering on tunable plasmonic nanoparticle substrates", Proc. Natl. Acad. Sci. USA 101, 17930 (2004). CrossRef H. Wang, C. S. Levin, N. J. Halas "Nanosphere Arrays with Controlled Sub-10-nm Gaps as Surface-Enhanced Raman Spectroscopy Substrates", J. Am. Chem. Soc. 127, 14992 (2005). CrossRef K. R. Brown, L. A. Lyon, A. P. Fox, B. D. Reiss, M. J. Natan, "Hydroxylamine Seeding of Colloidal Au Nanoparticles. 3. Controlled Formation of Conductive Au Films", Chem. Mater. 12, 314 (2000). CrossRef K. C. Grabar, R. G. Freeman, M. B. Hommer, M. J. Natan, "Preparation and Characterization of Au Colloid Monolayers", Anal. Chem. 67, 735 (1995). CrossRef K. Fujiwara, H. Kasaya, N. Ogawa, "Gold Nanoparticle Monolayer Formation on a Chemically Modified Glass Surface", Anal. Sci. 25, 241 (2009). CrossRef J. Turkevich, P. C. Stevenson, J. Hillier, "A study of the nucleation and growth processes in the synthesis of colloidal gold", Discuss. Faraday Soc. 11, 55 (1951). CrossRef K. C. Grabar, K. J. Allison, B. E. Baker, R. M. Bright, K. R. Brown, R. G. Freeman, A. P. Fox, C. D. Keating, M. D. Musick, M. J. Natan, "Two-Dimensional Arrays of Colloidal Gold Particles:? A Flexible Approach to Macroscopic Metal Surfaces", Langmuir 12, 2353 (1996). CrossRef J. H. Moon, J. H. Kim, K.-J. Kim, T.-H. Kang, B. Kim, Ch.-H. Kim, J. H. Hahn, J. W. Park, "Absolute Surface Density of the Amine Group of the Aminosilylated Thin Layers:? Ultraviolet?Visible Spectroscopy, Second Harmonic Generation, and Synchrotron-Radiation Photoelectron Spectroscopy Study", Langmuir 13, 4305 (1997). CrossRef B. Yan, A. Thubagere, W. R. Premasiri, L. D. Ziegler, L. Dal Negro, B. M. Reinhard, "Engineered SERS Substrates with Multiscale Signal Enhancement: Nanoparticle Cluster Arrays", ACS Nano 3, 1190 (2009). CrossRef N. Mohri, S. Matsushita, M. Inoue, K. Yoshikawa, "Desorption of 4-Aminobenzenethiol Bound to a Gold Surface", Langmuir 14, 2343 (1998). CrossRef